Attachment and Substance Use Disorders—Theoretical Models, Empirical Evidence, and Implications for Treatment - Schindler, Andreas (Frontiers in Psychiatry, 2019)
Introduction The article reviews attachment oriented research in individuals with substance use disorders (SUD). Based on attachment theory substance abuse can be understood as “self-medication”, as an attempt to compensate for lacking attachment strategies. Attachment theory suggests a developmental pathway from insecure attachment to SUD, and on the other hand a negative impact of substance abuse on attachment security. Additionally, differences due to different patterns of attachment, different substances, comorbid psychiatric disorders, and age groups are reflected. Methods Using medical and psychological databases 33 cross-sectional studies, three longitudinal studies, one systematic meta-analysis and six reviews were identified. Methodological problems such as poor assessment of SUD and the use of different measures of attachment limit comparability. Results Results of longitudinal studies clearly show insecure attachment to be a risk factor for SUD, while continued substance abuse impairs the ability to form close relationships. With regard to specific patterns of attachment results mainly point towards fearful and dismissing avoidance, while some studies report preoccupied and unresolved patterns. Results indicate different patterns of attachment in different groups of substance abusers. Fearful-avoidant attachment was frequent in heroin addicts while alcohol abusers had more heterogeneous patterns. The link between insecure attachment and SUD seems to be stronger in adolescence compared to adulthood. Discussion The last decades have seen a substantial growth in studies on attachment and SUDs. Today, the general link between SUD and insecure attachment is well established. However, connections between different patterns of attachment with different pathways towards SUD were also found, but data are still inconclusive. Evidence suggests that fostering attachment security and mentalization might improve the outcome of state-of-the-art treatment approaches in the field of SUD.